Enrichment of deleterious variants of mitochondrial DNA polymerase gene (POLG1) in bipolar disorder. Issue 8 (8th February 2017) - Kasahara, Takaoki; Ishiwata, Mizuho; Kakiuchi, Chihiro; Fuke, Satoshi; Iwata, Nakao; Ozaki, Norio; Kunugi, Hiroshi; Minabe, Yoshio; Nakamura, Kazuhiko; Iwata, Yasuhide; Fujii, Kumiko; Kanba, Shigenobu; et al.
Abstract : Aim: Rare missense variants, which likely account for a substantial portion of the genetic 'dark matter' for a common complex disease, are challenging because the impacts of variants on disease development are difficult to substantiate. This study aimed to examine the impacts of amino acid substitution variants in the POLG1 found in bipolar disorder, as an example and proof of concept, in three different modalities of assessment: in silico predictions, in vitro biochemical assays, and clinical evaluation. We then tested whether deleterious variants in POLG1 contributed to the genetics of bipolar disorder. Methods: We searched for variants in the POLG1 gene in 796 Japanese patients with bipolar disorder and 767 controls and comprehensively investigated all 23 identified variants in the three modalities of assessment. POLG1 encodes mitochondrial DNA polymerase and is one of the causative genes for a Mendelian‐inheritance mitochondrial disease, which is occasionally accompanied by mood disorders. The healthy control data from the Tohoku Medical Megabank Organization were also employed. Results: Although the frequency of carriers of deleterious variants varied from one method to another, every assessment achieved the same conclusion that deleterious POLG1 variants were significantly enriched in the variants identified in patients with bipolar disorder compared to those in controls. Conclusion: Together with mitochondrial dysfunction in bipolar disorder, the present results suggested deleterious POLG1 variants as a credible risk for the multifactorial disease.